ChemInform Abstract: Cu‐Mediated Direct Aryl C—H Halogenation: A Strategy to Control Mono‐ and Di‐Selectivity. Issue 30 (29th July 2014) - Du, Zhi‐Jun; Gao, Lian‐Xun; Lin, Ying‐Jie; Han, Fu‐She
Abstract Optimized reaction conditions are developed for the copper mediated ortho‐selective mono‐ and dihalogenation of 2‐phenylpyridines using acyl hypohalites, generated in situ from carboxylic acids and N‐halosuccinimides.